Electrical Conductivity and Ferromagnetism in a Reduced Graphene–Metal Oxide Hybrid. (27th August 2012) - Karim, Mohammad Razaul; Shinoda, Hideaki; Nakai, Mina; Hatakeyama, Kazuto; Kamihata, Hidenobu; Matsui, Takeshi; Taniguchi, Takaaki; Koinuma, Michio; Kuroiwa, Keita; Kurmoo, Mohamedally; Matsumoto, Yasumichi; Hayami, Shinya
Abstract The rare coexistence of ferromagnetism and electrical conductivity is observed in the reduced graphene oxide–metal oxide hybrids, rGO‐Co, rGO‐Ni, and rGO‐Fe, using chemical reduction with hydrazine or ultraviolet photoirradiation of the graphene oxide–metal complexes, GO‐Co, GO‐Ni, and GO‐Fe. The starting and final materials are characterized by X‐ray photoelectron spectroscopy, transmission electron microscopy (TEM), elemental analysis, Mössbauer spectroscopy, and Raman spectroscopy. In contrast to graphene, where the electrical conductivity and magnetic properties are controlled by carrier (electron or hole) doping, those of graphene oxide can be controlled by complexation with Co2+, Ni2+, and Fe3+ cations through the strong electrostatic affinity of negatively charged graphene oxide towards metal cations. The presence of ferromagnetism and electrical conductivity in these hybrids can promote significant applications including magnetic switching and data storage.